PlsX and PlsY: Additional roles beyond glycerophospholipid synthesis in Gram-negative bacteria - Audrey N. Rex; Brent W. Simpson; Gregory Bokinsky; M. Stephen Trent (mBio)
ABSTRACT The unique asymmetry of the Gram-negative outer membrane, with glycerophospholipids (GPLs) in the inner leaflet and lipopolysaccharide (LPS) in the outer leaflet, works to resist external stressors and prevent the entry of toxic compounds. Thus, GPL and LPS synthesis must be tightly controlled to maintain the integrity of this essential structure. We sought to decipher why organisms like Escherichia coli possess two redundant pathways—PlsB and PlsX/Y—for synthesis of the GPL precursor lysophosphatidic acid (LPA). LPA is then converted by PlsC to the universal precursor for GPL synthesis, phosphatidic acid (PA). PlsB and PlsC are essential in E. coli, indicating they serve as the major pathway for PA synthesis. While loss of PlsX or PlsY individually has little consequence on the cell, the absence of both was lethal. To understand the synthetic lethality of this seemingly redundant PlsX/Y pathway, we performed a suppressor screen. Suppressor analysis indicated that ∆plsXY requires increased levels of glycerol-3-phosphate (G3P), a GPL precursor. In agreement, ∆plsXY required supplementation with G3P for survival. Furthermore, loss of PlsX dysregulated fatty acid synthesis, resulting in increased long-chain fatty acids. We show that although PlsX/Y together contribute to PA synthesis, they also contribute to the regulation of overall membrane biogenesis. Thus, synthetic lethality of ∆plsXY is multifactorial, suggesting that PlsX/Y has been maintained as a redundant system to fine-tune the synthesis of major lipids and promote cell envelope homeostasis.IMPORTANCEGram-negative bacteria must maintain optimal ratios of glycerophospholipids and lipopolysaccharide within the cell envelope for viability. Maintenance of proper outer membrane asymmetry allows for resistance to toxins and antibiotics. Here, we describe additional roles of PlsX and PlsY in Escherichia coli beyond lysophosphatidic acid synthesis, a key precursor of all glycerophospholipids. These findings suggest that PlsX and PlsY also play a larger role in impacting homeostasis of lipid synthesis.